(untitled) (aSSIST Business Review, 2026)
This study investigates how Samsung LCD, a latecomer in the TFT-LCD industry, overtook Sharp—the market leader in the 1990s known for its technological dominance and overwhelming market share—to become the global No. 1. Applying the SER-M model (Subject–Environment–Resources–Mechanism), the Mechanism-Based View (MBV), and the Weight–Sequence Model (WSM), this case study provides a structured and multidimensional analysis of the strategic decisions and execution mechanisms that enabled Samsung’s turnaround. Samsung made a bold strategic move by investing preemptively in non-standard large-sized panels (12.1 and 13.3 inches), diverging from the prevailing industry focus on 10.4 and 11.3 inches. Notably, Samsung undertook this high-risk investment without securing prior demand, and later collaborated strategically with leading clients such as Toshiba and DELL to establish new market standards. This risk-bearing decision became the pivotal factor that catalyzed its success. By expanding the customer base and maximizing profits through these new products, Samsung continued to strengthen its position through successive preemptive investments in next-generation production lines. This strategic cycle was supported by a speed-oriented organizational culture characterized by rapid decision-making, a one-day response system closely aligned with customer needs, field-based problem-solving, and enterprise-wide alignment and execution. As a result, Samsung LCD overcame its technological and market disadvantages and successfully redefined the global market standard. This study offers meaningful implications for strategic planning by latecomer firms seeking to surpass incumbents in capital-intensive B2B industries.